Needs Analysis on English Language Learning of Software Engineering Students of SMK Kartika XX-1 Makassar - Sitti Nurjannah; Arini Nurwijayanti Ridwan (CV. Eureka Murakabi Abadi, 2022)
The objectives of this research were to determine: (1) the needs of software engineering students in learning English; and (2) the materials suit the English language learning of the software engineering students of SMK Kartika XX-1. This research used a descriptive qualitative research method. The participants of this research were 2 English teachers and 30 software engineering students grade X at SMK Kartika XX-1 Makassar, which were taken through purposive sampling. The instrument used in this research was a structured interview which was contained of 15 open-ended questions for students, and 10 open-ended questions for teachers. The data of this research were analysed in four stages; they were coding, data reduction, data display, and drawing conclusion or interpretation. As the result of this research, researcher found that the needs of Software Engineering students were to learn English in accordance with the teaching concepts of English for Specific Purposes. For necessities, both of the students and teachers stated that the students’ need speaking skill the most. Therefore, the lacks of students were the limitation of vocabularies and the less of self-confidence in speaking. In line with the students’ lacks, most of the students wanted their speaking skill and vocabulary achievement better than before. It can be concluded that some topic materials that covered four of language skills, they were; software language program for listening, software development for speaking, software introduction for reading, and the last was launch the computer program for writing.